All Hands-on Deck: Coordinated approaches to Indigenous early career development - Locke, Michelle; Trudgett, Michelle; Page, Susan (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2024)
The Developing Indigenous Early Career Researchers Project is a three-year longitudinal study funded by the Australian Research Council investigating the experiences and perspectives of Indigenous early career researchers working in universities across Australia. In an earlier paper we explored self-identified needs of Indigenous early career researchers regarding the development of sound research trajectories and careers in the academy (Locke et al., 2022). This paper takes a step further in investigating, who is responsible and should be held to account for supporting the development of these Indigenous early carer researchers. Data collected from across all three stages (2020, 2021 and 2022) of this project suggests that Indigenous early career researchers consider that all university staff, including themselves have certain responsibilities towards developing their academic career trajectories. Some Indigenous ECRs also pointed out the roles that external agencies such as government and funding bodies play in guiding institutions to value and promote the diversity and wealth of knowledge that Indigenous academics bring to the academy. This paper engages an Indigenist research approach and employs relatedness theory in advocating the development of policies and programs to support the career trajectories of Indigenous Early Career Researchers, from an Indigenous epistemological standpoint. To close, this paper posits that to achieve optimum outcomes for Indigenous ECR’s there needs to be systematic and coordinated institutional approaches to developing career trajectories that ameliorate challenges and barriers to Indigenous ECR career progression.